2019
DOI: 10.3389/fpubh.2019.00195
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dental Caries in Urban and Rural Children of the Riyadh Region of Saudi Arabia

Abstract: Background and Aim: The data presented in this study aimed to document caries prevalence and severity among a representative sample of 6, 12, and 15 years old Saudi Children. Methodology: The study examined a total of 1,986 school children from 75 schools in urban and rural areas of Riyadh region, Saudi Arabia. Children having one or more dental caries lesion were used to determine prevalence of dental caries. Total number of decayed filled teeth (dft) was used to assess cari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
1
19
0
2
Order By: Relevance
“…[ 37 ] Various factors, including socio-economic factors, sample size, dietary behaviors, brushing habits, and cultural differences, can lead to different results. [ 2 , 3 , 8 , 14 , 15 , 24 , 25 ] Thus, it is necessary to carefully and reasonably interpret each result. We speculate that the high incidence of DC in Jilin Province may be attributed to the following 2 factors:…”
Section: Resultsmentioning
confidence: 99%
“…[ 37 ] Various factors, including socio-economic factors, sample size, dietary behaviors, brushing habits, and cultural differences, can lead to different results. [ 2 , 3 , 8 , 14 , 15 , 24 , 25 ] Thus, it is necessary to carefully and reasonably interpret each result. We speculate that the high incidence of DC in Jilin Province may be attributed to the following 2 factors:…”
Section: Resultsmentioning
confidence: 99%
“…2,5,6,7,8 In this sense, rural life could expose individuals to limited access to both health services and fluoridated water, as well as to a low educational level, 9,10 all of which notably play a role in dental caries development. Whereas Al-Rafee et al 11 found no difference between rural and urban schoolchildren in this regard, controversial results revealed higher caries experience in urban populations. 12,13 This finding is conceivable, since living in an urban setting is known to increase exposure to unhealthy dietary habits, 12,14,15,16 and to allow easier access to industrialized and processed food.…”
Section: Introductionmentioning
confidence: 85%
“…The prevalence of caries in Saudi Arabia is remarkably high. For example, national statistics showed that the prevalence of dental caries was 71.35% among 15-year-old children in 2019 [ 6 ]. Moreover, a cross-regional meta-analysis conducted in 2010 showed a staggeringly high rate of caries among the Saudi population [ 7 ].…”
Section: Introductionmentioning
confidence: 99%